Characteristics of salt dust aerosols and their transport implications in the Aral Sea - Jie Liu; Jianli Ding; Bohua Liu; Shu Wu; Zhijuan Han (Scientific Reports)
Abstract Central Asia is an ecologically fragile arid zone and a typical mixed salt‒sand region. The socioeconomic and ecological problems attributed to the shrinking of the Aral Sea in Central Asia are notable concerns within the international community. In this study, the characteristics of salt dust aerosols from the Aral Sea were analysed to explore their interannual variation characteristics and analyse the spatial and temporal distributions of salt dust sources and transport and dispersion pathways. The results revealed that high concentrations of salt dust aerosols were concentrated around the Aral Sea and Lake Sarekamesh. The range and intensity of salt dust aerosols were less than those of dust aerosols. Salt dust events occurred frequently in spring and less frequently in autumn and winter. The occurrence frequency and impact range of salt dust aerosols from 2008 to 2012 were significantly lower than those during the previous period. From 2013 to 2018, the salt dust sources originated largely on the western side of the North Aral Sea. The spatial autocorrelation of salt dust aerosols was high and characterized by significant agglomeration, with significant changes in cold spot and hotspot regions. Salt dust in the Aral Sea region affects mainly the Kazakhstan region in spring, and it more notably affects Russia in winter. The results of this study increase the understanding of the spatial and temporal variability in salt dust aerosols within the arid zone of Central Asia and lay a foundation for the study of the impacts of salt dust aerosols on the climate system and ecological environment in arid zones.